Socioeconomic mobility and tobacco consumption patterns in fish industry workers in Udupi District of coastal Karnataka - Shashidhar Acharya; Kalyana Chakravarthy Pentapati; Shruthi Acharya (Wolters Kluwer Medknow Publications, 2014)
Aim: The aim of this study was to understand the tobacco consumption patterns and their relationship with life course socioeconomic mobility among fish industry workers as this could provide important information in dealing with the tobacco problem in this very vulnerable population. Materials and Methods: Socioeconomic life course data and information about tobacco habits was collected from 102 fish industry workers. A subject was considered to be upwardly mobile if the family head's educational attainment and the number of earning members increased and the number of children and dependents decreased since childhood in his or her household. Oral examination was also done for malignant/premalignant lesions. Results: Of the 102 subjects, 64 regularly consumed tobacco either in smoking or smokeless forms and the common reasons for the habit were the co-workers' influence and to keep awake at work. Fourteen subjects had premalignant lesions in the oral cavity and all them were in the buccal mucosa. The prevalence of the tobacco habit was much lesser (25%) among the upwardly mobile group when compared to the minimal or no improvement group (75%). A majority of those free from the habit (73.7%) were belonging to the group, which showed improved educational attainment. Among those with good social mobility, the percentage of workers with high frequency of tobacco consumption and those with a longer duration of the tobacco habit was low when compared to the minimal social mobility group. Conclusion: A holistic approach consisting of efforts to improve the overall socioeconomic conditions can be more effective than piecemeal solutions in dealing with the tobacco menace.